Parameter estimates for additive breed genetic and heterotic effects for preweaning traits of dairy calves in coastal lowland Kenya - Kahi, A.K.; Thorpe, W.R.; Baker, R.L. (South African Society of Animal Science, 1996)
A total of 1443 records of preweaning traits of calves in a dairy herd in coastal lowland Kenya were used to estimate crossbreeding parameters in a regression analysis. In this herd, the Ayrshire (A), Brown Swiss (B) and Sahiwal (S) breeds have been used in a 3-breed rotation crossbreeding system. Records of birth weight (BW), average daily gain from birth to weaning (DG) weaning age (WA( and calf survival to weaning (SR) were analysed. Calves were weaned at a fixed weight of 90 kg. The individual and maternal additive genetic effects for A and S were not significant (P>0.05) for calf performance. Similarly, the individual heterotic effect of Bos taurus-B. indicus heterozygosity was not significant for calf performance. A small effect of AS indicidual heterosis on DG was found. It was estimated that F1 AS calves grew 26 g/day faster (P<0.1) than the mean of the purebred A and S. The maternal heterotic effect of B. taurus-B. indicus heterozygosity for BW was -3.19+1.25 kg (P<0.05). Most estimates Reported in the literature are of opposite sign. The individual and maternal breeds and heterotic effects of the sire and dam genotypes summed to give very similar aggregate preweaning performance. It was concluded that preweaning performance should be given little emphasis in this herd when selecting among these breeds, and crossbreeding systems. Breeding decisions will be determined by relative lactation and reproductive performance of cows.